An Improved PCR‐RFLP Assay for the Detection of a Polymorphism rs2289487 of PLIN1 Gene. Issue 6 (13th April 2016) - Feng, Xiaolei; Wang, Sihua; Duan, Xiaoran; Li, Chunyang; Yan, Zhen; Feng, Feifei; Yu, Songcheng; Wu, Yongjun; Wang, Wei
Abstract : Background: In recent research, it has been shown that rs2289487 within the PLIN1 gene has different variants that have been associated with obesity, type 2 diabetes, and other diseases. However, the isochizomers such as the BsmI enzyme required for detection of this polymorphism through polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) method are expensive. In this study, we aimed to explore a novel PCR‐RFLP method for identifying the single‐nucleotide polymorphism (SNP) of rs2289487 of PLIN1 gene. Methods: A new restriction enzyme site was created through created restriction site PCR. In the forward primer, a deoxynucleotide A was substituted with C, and after PCR a new restriction enzyme site for BstUI was introduced into the PCR products. A total of 108 samples from Han Chinese were tested to evaluate this new method. Results: Allele frequencies in the Asian population were 0.326 for allele A and 0.674 for allele G, and the genotype frequencies were 12.8% for AA, 39.5% for AG, and 47.7% for GG. Conclusion: The PCR‐RFLP with new site for detecting the SNP of rs2289487 is an improved method with low cost and high accuracy.